2016
DOI: 10.1080/01616412.2016.1190121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bell’s palsy in Qena Governorate, Egypt

Abstract: The overall prevalence and incidence rates of BP in Qena governorate were high. This could be related to the variation in day and night temperature in our community and the susceptibility to air draft exposure during the night. The high frequency of poor outcome among studied cases suggests that better local guidelines should be implemented to recognize and treat BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The result showed the number of cases per month was significantly and negatively was significantly and negatively correlated with the summer months and mean monthly temperatures (p = 0.002 and < 0.000, respectively) and strong positive correlation with monthly wind chill factor (p < 0.000). Wind chill factor is a novel, reliable estimator of the overall meteorological factorsderived risk [83] A community-based research in Qena Governorate, Egypt confirmed the most frequent precipitating factors for an episode of Bell's palsy were exposure to air draft in 40%. This could be related to variations between day and night temperatures in their community.…”
Section: Anatomical Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The result showed the number of cases per month was significantly and negatively was significantly and negatively correlated with the summer months and mean monthly temperatures (p = 0.002 and < 0.000, respectively) and strong positive correlation with monthly wind chill factor (p < 0.000). Wind chill factor is a novel, reliable estimator of the overall meteorological factorsderived risk [83] A community-based research in Qena Governorate, Egypt confirmed the most frequent precipitating factors for an episode of Bell's palsy were exposure to air draft in 40%. This could be related to variations between day and night temperatures in their community.…”
Section: Anatomical Structurementioning
confidence: 99%
“…These results suggest that the wind chill factor, which depends on both temperature and wind speed, is a novel, reliable estimator of the overall meteorological factor derived risks that influence the probability of BP occurrence. Furthermore, a community-based study was conducted to assess the factors that precipitated cases of BP in Qena Governorate, Egypt [83]. The most frequent precipitating factors were exposure to air draft (40%) and upper respiratory tract infection (13.3%).…”
Section: Acute Cold Exposurementioning
confidence: 99%
“…Bell's palsy is most likely to represent an autoimmune reaction in response to a component of the peripheral nerve myelin, leading to demyelination of the facial nerve (Greco et al, ). This autoimmune disease can be triggered by a viral infection as well as acute cold (Jeon et al, ; Khedr et al, ; Kokotis & Katsavos, ; Wakisaka et al, ) and accounts for 60%–75% of all cases of unilateral facial paralysis (Adel, Kawthar, Amine, Youssef Souha, & Abdellatif, ). Subcutaneous fat is the primary line of defense against cold stimuli, which can release various secretory factors or adipokines that signal the immune system (Huh, Park, Ham, & Kim, ; Vielma, Klein, Levingston, & Young, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidence from epidemiological studies has shown that the incidence of Bell's palsy is related to temperature and cold wind factors (Franzke et al, ; Kokotis & Katsavos, ; Spengos et al, ; Zhao et al, ). Specifically, the incidence of Bell's palsy was found to increase during cold days or in regions with a large diurnal temperature difference, indicating that a sharp temperature change may be one of the risk factors for facial palsy (Hsieh, Wang, & Lee, ; Khedr et al, ). The adipose tissue provides protection against cold stimuli and is also considered to be an endocrine organ capable of releasing various secretory factors or adipokines (Kuryszko, Slawuta, & Sapikowski, ; Wang, Mariman, Renes, & Keijer, ).…”
Section: Introductionmentioning
confidence: 99%
“…A study from the Benghazi region of Libya showed people above the sixth decade in age as being prone to Bell's palsy [3]. This was at variance with neighbouring Egypt whose findings showed the highest ages of involvement to be 40-49 years [12]. A door-door survey in the rural part of the Cordillera province of Bolivia however, found similarly to the Libyan study with the prevalence of Bell's palsy increasing with age to peak at 65 years [13].…”
Section: Age and Bell's Palsymentioning
confidence: 97%